CLINICAL AND LABORATORY EVALUATION OF INTOXICATION SYNDROME IN CHILDREN WITH ACUTE RESPIRATORY VIRAL INFECTIONS - O. M. Ibragimova; L. A. Alekseyeva; I. V. Babachenko; T. V. Bessonova (LLC "Diagnostics and Vaccines", 2015)
There was performed a comparative analysis of clinical and laboratory indicators of intoxication syndrome in 70 children aged from 1 month to 16 years with acute respiratory viral infection (АRVI) of different etiology. To make an objective appraisal of the intoxication syndrome intensity the spectral characteristics of low and median molecular weight substances (LMMWS) in plasma and red blood cells with the calculation of their balance was studied, the level of exogenous pathogens was defined. The intensity of clinical symptoms was evaluated in points (from 0 to 3). It was established that total clinical manifestation of intoxication syndrome was from 3,4 ± 0,6 points in the case of respiratory syncytial viral infection to 6,2 ± 0,8 points in the case of influenza depending on the etiology. The increased level of LMMWS in red blood cells and exogenous pathogens was noticed to compare with the control values in all the groups regardless of the etiology. In the case of influenza the increase of LMMWS in plasma to 11,5 ± 0,5 c.u., and of the level of exogenous pathogens to 0,25 ± 0,04 c.u. was noted. The most expressed changes of indicators were revealed in the case of mixed viral infection when LMMWS in plasma was increased to 14,0 ± 1,6 c.u., LMMWS in red blood cells - to 27,0 ± 1,2 c.u., and exogenous pathogens amount - to 0,4 ± 0,09 c.u. A direct correlation of the average force between clinical and laboratory criteria of intoxication was revealed (r = 0,3; p < 0,05).